On the Sociology’s Contribution to Knowledgeof the Baltic Way - Lauristin, Marju; Norkus, Zenonas; Vihalemm, Peeter (Sociologija. Mintis ir veiksmas, 2011)
The goal of this article is to identify the lacunae in recent research about post-Communist transformations in the Baltic states, a task for which sociology as a social-scientific discipline is uniquely qualified. The paper starts by periodising the two decades of post-Communist transformation which applies across all three Baltic states, providing evidence for a common Baltic way, with Estonia in a pioneering role. This is corroborated by quantitative evidence comparing post-Communist countries in terms of performance. According to received transitological wisdom, economic or political processes (shock therapy or anti-Communist revolution) were decisive factors in the early success of post-Communist transformation. In contrast, this article argues that economic and political explanations are insufficient in accounting for the running order between Baltic states, and calls instead for sociological explanations focusing on cultural differences described in terms of four orientations of the social imaginary and of social action – continuational, restitutive, emulative and innovative.
Keywords: post-Communist transformation; the Baltic way; shock therapy versus gradualism; elite exchange; orientations of the social imaginary and social action